FACTORS ASSOCIATED WITH MOTIVES FOR FOOD CHOICE IN STUDENTS OF SMKN 3 BOGOR CITY, WEST JAVA, INDONESIA - Pujiyanti, Suci; Fikawati, Sandra; Islamiati, Nisa Nur (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
Important factors that influence a person in choosing their food. Adolescence is the time when a person begins to make choices, including choosing what foods they like and don't like to consume. This study aims to know the factors related to food choice motives among students at SMKN 3 Bogor City, West Java, Indonesia. The research design was Cross-sectional. Respondents were students of SMKN 3 Bogor class X, XI, and XII from five different majors, equalling 369 students were selected according to the inclusion criteria (students at SMKN 3 Kota Bogor) and exclusion criteria (students on special disease diets, students belonging to the vegan, vegetarian and pescetarian groups, students with certain food allergies). The results showed that the respondents who are frequently exposed to social media pay more attention to food choice motives compared to those who are less exposed to social media with a p-value <0.05. It can be concluded that social media as an important variable in determining food choice motives in adolescents must be a concern. The management of information dissemination carried out on social media should have regular regulations and legal sanctions if violations occur so that the information received is based on facts and can educate societies. Healthy food preferences still need to be enhanced among teenagers, and the promotion of healthy and natural foods should be intensified with breakthrough approaches